ТНЕ INVESTIGATION OF THE INFLUENCE OF FUEL DISTINCTION TEMPERATURE ON ITS MAIN PHYSICO-CHEMICAL INDICATORS - GANZYUK, ALLA; MASLO, LESYA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Widespread and indispensable growth of natural adsorbents use is caused by the fact that they, having developed specific surface and good (often specific) bleaching peculiarities, are dozens of times cheaper than artificial adsorbents. It leads to simplification of its usage technology – they often exclude the regeneration stage from the scheme. Chemical and thermal stability of saponite, as well as ion exchange properties, open opportunities for the creation of porous materials based on natural minerals with controlled properties that can replace synthetic analogues, the production of which is associated with high technological costs. The increase in the use of natural adsorbents is based on its specific surface area and good bleaching properties which are ten times cheaper than artificial adsorbents. In this regard, the technology of their application is simplified: the regeneration stage is often excluded from the scheme. Chemical and thermal stability of saponites, as well as ion exchange properties, open up new avenues for the creation of porous materials based on natural minerals with controlled properties that can replace synthetic analogues, the production of which is associated with high technological costs. The expediency of purification of hydrocarbon mixtures using granular saponite to obtain high-octane fuels has been studied. The influence of fuel distillation temperature on its main physicochemical parameters has been studied. The fractional composition of fuel, which is affected by such indicators as: engine warm-up speed, wear of the cylinder-piston group have been investigated. The obtained results of investigations of structural, physic and chemical properties of natural minerals allow to develop theoretical and practical bases of target change of the complex of specific properties that satisfy the basic requirements, which are put forward for sorption materials. The chemical and thermal stability of glauconites, as well as ion-exchange properties, provide opportunities for the production of porous materials based on natural minerals with controlled properties that can replace synthetic analogues associated with high technological costs.